Thrombocytosis: can it be used as a marker for tuberculosis? - Rathod, Suman; Samel, Dinesh Ramesh; Kshirsagar, Prasita; Pokar, Muddasir (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is a major health problem in India. Early diagnosis and prompt treatment is the key to control this menace. Hence to improve diagnosis in peripheral region, it is imperative that other methods are used to supplement the diagnostic This study aimed at assessing the reactive thrombocytosis in patients with tuberculosis admitted in medicine ward of RGMC and CSMH, Kalwa, Thane, India. Methods: This study was conducted from 1st January 2016 up to 31st June 2016. Data was collected from the PM register and also from Post mortem records, entered in MS Excel and analyzed. Results: Newly discovered, 112 patients, diagnosed on basis of sputum AFB positivity, chest x-ray changes, pleural fluid, ascitic fluid and CSF analysis reports suggestive of tuberculosis were selected to be the cases, out of which 50 were males (44.6%) and 62 females (55.4%)and, 127 non-tuberculous patients admitted for other causes who did not have any symptoms or signs of tuberculosis were randomly selected to be the control group of the study. The ages of the patients ranged from 14 to 76 years old. Thrombocytosis was detected in 84 (75%)of the Tb patients, whereas only 3 (2.3%) in Non-Tb Patients. The erythrocyte sedimentation rate (ESR) was increased by more than 20 in 97.4% of the patients. Conclusions: The changes in these parameters (platelets count and ESR) may reflect a reaction to the inflammatory condition. Therefore, in endemic areas, the presence of such haematological peripheral blood changes may raise the suspicion of pulmonary tuberculosis.